Retinal microglia: Just bystander or target for therapy?. (March 2015) - Karlstetter, Marcus; Scholz, Rebecca; Rutar, Matt; Wong, Wai T.; Provis, Jan M.; Langmann, Thomas
Abstract: Resident microglial cells can be regarded as the immunological watchdogs of the brain and the retina. They are active sensors of their neuronal microenvironment and rapidly respond to various insults with a morphological and functional transformation into reactive phagocytes. There is strong evidence from animal models and in situ analyses of human tissue that microglial reactivity is a common hallmark of various retinal degenerative and inflammatory diseases. These include rare hereditary retinopathies such as retinitis pigmentosa and X-linked juvenile retinoschisis but also comprise more common multifactorial retinal diseases such as age-related macular degeneration, diabetic retinopathy, glaucoma, and uveitis as well as neurological disorders with ocular manifestation. In this review, we describe how microglial function is kept in balance under normal conditions by cross-talk with other retinal cells and summarize how microglia respond to different forms of retinal injury. In addition, we present the concept that microglia play a key role in local regulation of complement in the retina and specify aspects of microglial aging relevant for chronic inflammatory processes in the retina. We conclude that this resident immune cell of the retina cannot be simply regarded as bystander of disease but may instead be a potential therapeutic target to be modulated in the treatment of degenerative and inflammatory diseases of the retina.